Analisis Pemanfaatan Internet Di Pemerintah Kota Denpasar - andyka, made; linawati, Linawati; Widyantara, I Made Oka (Jurnal Teknologi Elektro; Vol 15 No 2 (2016): (July - December) Majalah Ilmiah Teknologi Elektro, 2016)
The usage of the Internet can be described by the traffic characteristics, user behavior, and bandwidth. This research collected Internet traffic data at the government office of Denpasar city in October 2015, for study case of Dinas Perijinan . The result shows the average 90 % volume of TCP protocol and 10 % of others, such as UDP, GRE, and ICMP. There are average 9 5 % of application port’s volumes were used by IANA’s port, and 5 % by unsigned port, which means it may become a potential to be used as malware and file sharing application. The biggest domain’s volumes were accessed to Youtube and Facebook websites, and also to other malware domain. Based on the observation of user's behaviour, there are 3 of 12 sample users did not understand how to access good link from malware. From the analysis, a limitation access on youtube is one of recommendation actions besides closing malware port and user training.
Keywords: Traffic Characteristics, internet user behavior, traffic analysis